Semiautomatic Determination of Arterial Input Function in DCE-MRI of the Abdomen - Kim, Harrison; Morgan, Desiree E (British Journal of Healthcare and Medical Research, 2017)
The goal of this study was to develop a semiautomatic segmentation technique of the abdominal aorta to determine the arterial input function (AIF). A total of 24 patients having therapy naïve abdominal cancers were imaged using DCE-MRI on a 3T MR scanner. DCE-MRI continued for 4.2 minutes with 2.1 seconds temporal resolution (120 acquisitions). Gadoteridol (0.1 mmol/kg) was infused intravenously at 30 seconds after starting DCE-MRI, and flushed with 20-ml saline (2 ml/s). Patients were instructed to hold breath after maximal inhalation, and repeat as needed to full inspiration. The location of the abdominal aorta was manually identified, but its segmentation and motion tracking were automatically implemented. AIFs determined in the aortic region with and without tracking motion were statistically compared. The aortic region was further segmented into multiple smaller regions, and the AIF change according to the size of the region of interest (ROI) was examined. The displacement of the abdominal aorta during DCE-MRI was 3.4±2.3 (mean±SD) mm. The root mean square error (RMSE) of AIF from the best fitting curve was 0.110±0.010 mM after motion correction, which was significantly smaller than that before motion correction (0.134±0.016 mM; p<0.001). The amplitude of AIF varied up to 15% according to the ROI size. However, when the radius of ROI was reduced more than 3 mm, the variation in AIF amplitude was less than 5%. Therefore the ROI having smaller radius than that of aorta will need to be used to determine a reliable AIF in abdominal DCE-MRI.